Properties and Differential Expression of H+ Receptors in Dorsal Root Ganglia: Is a Labeled-Line Coding for Acid Nociception Possible? - Páez, Omar; Segura-Chama, Pedro; Almanza, Angélica; Pellicer, Francisco; Mercado, Francisco (Frontiers in Physiology, 2021)
Pain by chemical irritants is one of the less well-described aspects of nociception. The acidic substance is the paradigm of the chemical noxious compound. An acidic insult on cutaneous, subcutaneous and muscle tissue results in pain sensation. Acid (or H+) has at least two main receptor channels in dorsal root ganglia (DRG) nociceptors: the heat receptor TRPV1 and the acid-sensing ionic channels (ASICs). TRPV1 is a low-sensitivity H+ receptor, whereas ASIC channels display a higher H+ sensitivity of at least one order of magnitude. In this review, we first describe the functional and structural characteristics of these and other H+-receptor candidates and the biophysics of their responses to low pH. Additionally, we compile reports of the expression of these H+-receptors (and other possible complementary proteins) within the DRG and compare these data with mRNA expression profiles from single-cell sequencing datasets for ASIC3, ASIC1, TRPA1 and TRPV1. We show that few nociceptor subpopulations (discriminated by unbiased classifications) combine acid-sensitive channels. This comparative review is presented in light of the accumulating evidence for labelled-line coding for most noxious sensory stimuli.